Modeling of high power led illumination distribution using ann - (:unkn) unknown (My University, 2009)
High power light emitting diodes (HP-LEDs) are more suitable for energy saving applications and have becoming replacing traditional fluorescent and incandescent bulbs for its energy efficient. Therefore, HP-LED lighting has been regarded in the next-generation lighting. In this study, illumination distribution of white color HP-LED was examined and modeled by artificial neural network (ANN) to use at the different lighting applications. Illuminance measurements were done at different distances and voltage levels in the isolated test room. The obtained data was used to model the HP-LED illuminance distribution by ANN. As the realized ANN model, it was presented illumination distribution graphs. Matlab's Neural Network Tool box was used for the simulations.